RE: Risk of HBV Reactivation in HBsAg Negative and AntiHBc IgG Positive Patients Receiving Biologic Therapy - Ergenç, İlkay and Kani, Haluk Tarık and Karabacak, Murat and Cömert Özer, Elif and Mehdiyev, Shahin and Jafarov, Fuad and Abacar, Kerem Yiğit and Kutluğ Ağaçkıran, Seda and Sevik, Gizem and Aslan, Rahmi and et al. (Turkish Journal of Gastroenterology, 2023)
Cite this article as: Ergenç İ, Kani HT, Karabacak M, et al. RE: risk of HBV reactivation in HBsAg negative and anti-HBc IgG positive patients receiving biologic therapy. Turk J Gastroenterol. 2023;34(3):310.